Cross-Sectional Study on Overweight and Obesity Associated with Fast-Food Consumption in Bangladesh - Sultana, Farhana; Siddiqui, Shafayet Ahmed; Islam, Md. Ashraful; Al Muktadir, Mohammad Hamid; Millat, Md. Shalahuddin; Islam, Muhammed Mohibul; Tareq, Abu Montakim; Afroz, Nahida; Rahman, Mahabuba; Amin, Mohammad Nurul; Emran, Talha Bin (UI Scholars Hub, 2022)
Background: This study aimed to investigate the risk factors and status of fast-food consumption among students in Bangladesh. Methods: This cross-sectional study was conducted from March to November 2020. A total of 654 samples were collected from several schools, colleges, and universities during this study period. Results: About 60.1% and 39.9% of the students were male and female, respectively. Of the students, 53.1% considered fast food as unhealthy (p < 0.001), but only 47.7% were leading a sedentary lifestyle. A significant outcome of overweight and pre-obesity was observed for student institutions, consumption frequency, daily fast-food consumption, and sedentary lifestyle (p < 0.001). In addition, positive association was observed for fast-food consumption more than three times and less than three times per week (OR and 95% CI: 11.13 [7.52–16.47], p < 0.001), higher social class and lower class (OR and 95% CI: 2.18 [1.31–3.62], p = 0.003), fast food preference and other foods (OR and 95% CI: 1.55 [1.11–2.15], p = 0.009), and sedentary and heavily active lifestyle (OR and 95% CI: 5.71 [2.02–16.10], p = 0.001) using logistic regression. Conclusions: Overweight and obesity are serious public health concerns, which are highly associated with fast-food consumption along with lifestyle, economy, and fast-food preference among students in Dhaka City, Bangladesh.